PENGARUH ANGGARAN BIAYA MATERIAL SEBAGAI ALAT PENGENDALIAN BIAYA PADA PERUSAHAAN PT. MEGATAMA PROPINDO MAKASSAR - Irwandi, Syahrul; Jumarti; Iskandar, Sultan; Andi Badrussaman (Jurnal Unicorn ADPERTISI, 2024)
The purpose of this research is to determine whether the budget for material costs can be used as a measure in cost control at PT. Megatama Propindo Makassar. The types of data used in this study are: Qualitative Data, which are observation results in categorical form rather than numerical. Quantitative Data, which are observation results measured on a numeric or numerical scale. The data sources used in this  study  are:  Primary  Data,  obtained  from  observations  and  interviews  with  employees  of  PT. Megatama Propindo Makassar to obtain data related to the research problem for further processing. Secondary Data,  obtained  in processed  form in  company documents such  as a  brief  history of the company, organizational structure, material budget data, and its realization. The data collection methods used are: Observation, a method of direct observation of the object being studied to collect necessary data. Interview, a method of gathering information obtained by asking questions to employees in the finance/accounting and administrative departments. Documentation, a method of collecting data by analyzing documents in the company, such as plans for preparing project material budget reports and project material costs. The material cost budget functions as a tool for cost control at PT. Megatama Propindo Makassar by comparing the budget with the actual realization. Thus, it can be determined that there  is  a  difference  in  material  costs  amounting  to  IDR  984,926,992  from  a  budget  of  IDR 6,007,287,270, and actual realization of IDR 5,022,360,278. This is due to the fact that the actual material cost is smaller than the material cost budget by IDR 983,530,992 and the actual material cost is greater than the material cost budget by IDR 1,396,000. The company can record these deviations as favorable or unfavorable